Assessing the impact path of air quality on enterprise R&D investment: Empirical evidence from dual perspectives of investor sentiment and government concern - Yang, Jialiang; He, Dan; Qureshi, Naveed Akhtar (Frontiers in Environmental Science, 2022)
Based on the data of Shanghai and Shenzhen A-share listed companies from 2015 to 2019, this paper studies the influence of air quality on the R&D investment of listed companies from the perspectives of investor sentiment and government concern. It is found that, on the whole, air quality has a significant inhibitory effect on R&D investment. Air quality significantly promotes investor sentiment, which serves as a path to further restrain the R&D investment of listed companies. Air pollution is an effective concern for the government and serves as a veil between air quality and R&D investment. Furthermore, this paper analyzes the heterogeneity of enterprises from the aspects of regional technology complexity, property right nature, whether it is a polluting enterprise or not, and whether it is a key regulated enterprise or not, and comes to relevant conclusions. This paper expands the research on air quality and enterprise R&D investment decision-making, which helps to clarify and improve the transmission mechanism and implementation effect of environmental protection policies.